Semiotic in Wednesday Series Created by Alfred Gough and Miles Millar - Raz, N. Tiru; Sembiring, Milisi; Sitinjak, Vivi Novalia (PT FORMOSA CENDEKIA GLOBAL, 2024)
A literary work is a forum for the expression of the writer's ideas, beliefs, physical experiences, and the writer's imagination. Language in the form of symbols is interesting to study semantically. Semiotics is the study of symbols in three aspects: icons, indices, and symbols. The Wednesday series, created by Alfred Gough and Miles Miller, tells the story of a young girl who is strictly forced to study at a school named Nevermore Academy. This school is for freaks and outcast students, and she does not want to be in it. She does not like this school, but as time goes on, she grows to like it even more, with all of its mysteries, sadism, people, and monsters. The questions of this study are (1) how is the semiotic aspect of symbolism included in “Wednesday,” (2) how is the indexical aspect of semiotics included in “Wednesday,” and (3) how is the semiotic aspect of symbolism included in “Wednesday”? This study uses qualitative methods. The results of this study are 33 data for icons in the entire series of Wednesdays created by Alfred Gough and Miles Millar. 21 data for an index of the entire series of Wednesdays created by Alfred Gough and Miles Millar. 21 data for an index of the entire series of Wednesdays created by Alfred Gough and The symbols for all series of Wednesday created by Miles Millar are 6 data